Carbon black–polybenzoxazine nanocomposites for high K dielectric applications. Issue 11 (22nd January 2014) - Selvi, M.; Devaraju, S.; Sethuraman, K.; Alagar, M.
<x xml:space="preserve">Abstract</x> This work involves the development of surface functionalized carbon black (FCB) reinforced polybenzoxazine (PBZ) nanocomposites, using a benzoxazine monomer and varying weight percentages of functionalized carbon black (0.5, 1.0, and 1.5 wt%) through ring opening polymerization via thermal cure. Data from the morphological studies indicate that the nanosized FCB particles are homogeneously distributed in the polybenzoxazine matrix. The incorporation of FCB improves the dielectric constant, electrical conductivity, and reduction in resistivity of the resulting FCB–PBZ nanocomposites when compared to neat PBZ. A significant improvement observed in glass transition temperature and thermal stability of resulting FCB–PBZ nanocomposites, when compared to neat PBZ. POLYM. COMPOS., 35:2121–2128, 2014. © 2014 Society of Plastics Engineers